(untitled) (Fiep Bulletin - online, 2014)
Cigarette smoking is the main risk factor for preventable chronic diseases, including peripheral arterial disease (PAD) and chronic obstructive pulmonary disease (COPD). It is considered important to assess lung function in arteriopathic patients, since the association with lung disease can also limit the exercise capacity of these individuals. OBJECTIVE: To evaluate the smoking habit, lung function, the ankle-brachial index (ABI) and walking capacity from individuals with PAD, and check if there are correlations between respiratory and peripherals indices. METHODOLOGY: Analysis of data from medical records of patients with PAD. Data: 1) personal characteristics; 2) data related to smoking; 3) pulmonary function data; 4) ABI; 5) claudication test. RESULTS: BMI and age did not correlate significantly with any other parameters. There were no statistically significant correlations between the index of smoking and vascular or respiratory parameters. Spirometric data were significantly correlated between them, but not with other parameters. The relationship indicated by the literature that the greater the intensity of smoking, the greater the tendency to impairment of lung function is true, but not mandatory, since all individuals in the study were smokers, but not all are COPD. The continuity of this research may indicate greater statistical power, whether there is correlation between the peripheral and respiratory variables in individuals with PAD, as it has not yet found in the literature. CONCLUSION: In this sample of patients with moderate PAD smoking and COPD have a high prevalence. Although there was no correlation between vascular and respiratory data, it is believed that the pulmonary function should be investigated in patients with PAD smokers to optimize their treatment.